(untitled) (Research, Society and Development, 2022)
This research aims to demonstrate the relationship between Social Inequality in the country and the increase in the rates of Infractions. This relationship is demonstrated through notes about the violation of the Doctrine of Integral Protection - one of the basic principles that govern the Rights of Children and Adolescents - and Human Dignity, as well as through statistical data on the economic and psychological conditions in where children and adolescents who commit Infractional Acts are found. In addition, it explains the influence of family structure in the practice of these Acts. Faced with the violation of this principle and the family and affective lack faced, many children and adolescents begin to practice Infractional Acts, as a way of filling this lack and in some cases, as a way of survival. With this, the general objective of the research is to demonstrate the influence of the social context in which the individual who practices Infractions is inserted. Specifically, it seeks to draw notes about the violation of the Principles of Human Dignity and Comprehensive Protection; to discuss the situation of social vulnerability in which children and adolescents who are perpetrators of Infractional Acts find themselves; to analyze studies with regard to the relationship and influence between the lack of family structure and the practice of infractions. To this end, bibliographic research and statistical data on social inequality and infractions were used. In this sense, the Social Inequality index in the last 20 years directly reflected the increase in Infractions in Brazil.